Development of Students' Spiritual Intelligence through the Learning Process of Christian Religious Education at Budi Murni 2 Medan Catholic Private Senior High School - Aldi Alfrianza Sinulingga; Abdi Guna Sitepu; Jeninta Rasbina Br Barus; Ermina Waruwu (International Journal of Scientific Multidisciplinary Research, 2023)
This study aims to answer research problems regarding development of students' spiritual intelligence through the learning process of christian religious education at Budi Murni 2 Medan Catholic Private Senior High School.This study uses a descriptive qualitative approach. Researchers conducted research at Budi Murni 2 Medan Catholic Private Senior High School from March to April 2023. The research subjects are selected by purposive sampling. The informants identified in this study are 11 people, namely the vice principal, religion teacher, and 9 students. Data analysis is carried out by means of data reduction, data presentation, and research conclusions.The results of the study show that the development of students' spiritual intelligence is carried out by the teacher through the role of the religious teacher as a good spiritual shepherd for students, helping students fulfill their life mission, inviting students to read the scriptures, involving students in religious activities. Aspects of spiritual intelligence include self-awareness, spontaneity, caring, celebrating diversity, the ability to reframe, and humility